BEHAVIOR PATTERNS IN THE SYSTEM OF HIGHER EDUCATION - Ekaterina I. Trubnikova (Высшее образование в России)
The article investigates the formal and informal restrictions in the system of higher education in Russia, explores the behaviour patterns generated by various restrictions. The frameworks are imposed not only by the regulator and by university authorities, but also by the society. There were analyzed various methods that are used by an administration (the issues of mobbing, the mechanism of gift exchange, the possibility of opportunistic behavior). Special attention is paid to the fact of increasing value of the teaching load in University and mechanisms of the distribution of this particular resource within higher education institutions. The university teacher depends on the informal requirements of the institution, which ultimately shape not only his (her) behavior, but also affects his (her) views and beliefs.